2013
DOI: 10.1371/journal.pntd.0001954
|View full text |Cite
|
Sign up to set email alerts
|

A Single Multilocus Sequence Typing (MLST) Scheme for Seven Pathogenic Leptospira Species

Abstract: BackgroundThe available Leptospira multilocus sequence typing (MLST) scheme supported by a MLST website is limited to L. interrogans and L. kirschneri. Our aim was to broaden the utility of this scheme to incorporate a total of seven pathogenic species.Methodology and FindingsWe modified the existing scheme by replacing one of the seven MLST loci (fadD was changed to caiB), as the former gene did not appear to be present in some pathogenic species. Comparison of the original and modified schemes using data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
200
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 33 publications
10
200
1
8
Order By: Relevance
“…This is also observed with the new MLST protocol [25] in which serovar Pomona can be assigned to STs 38 and 140 together with serovars Gem and Guaratuba, respectively. Although MLST techniques enable Leptospira species differentiation [9,25], serovar assignment still needs improvement. Only when molecular methods ensure species and serovar identification, will they completely replace serological methods.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This is also observed with the new MLST protocol [25] in which serovar Pomona can be assigned to STs 38 and 140 together with serovars Gem and Guaratuba, respectively. Although MLST techniques enable Leptospira species differentiation [9,25], serovar assignment still needs improvement. Only when molecular methods ensure species and serovar identification, will they completely replace serological methods.…”
Section: Discussionsupporting
confidence: 53%
“…As MLST does not always specify Leptospira serovars [9], the same ST 37 also encompasses serovar Canicola when using the scheme previously proposed [19,9,11]. This is also observed with the new MLST protocol [25] in which serovar Pomona can be assigned to STs 38 and 140 together with serovars Gem and Guaratuba, respectively. Although MLST techniques enable Leptospira species differentiation [9,25], serovar assignment still needs improvement.…”
Section: Discussionmentioning
confidence: 85%
“…PFGE is useful for identifying leptospiral serovars (Herrmann et al, 1992), but the resulting complex patterns may be challenging for interlaboratory pattern comparisons. MLST has also been used for Leptospira species genotyping (Boonsilp et al, 2013). However, our previous study demonstrated that MLST was unsuitable for serovar (or serogroup) identification and had less discriminatory power than PFGE .…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] In addition, multilocus sequence typing (MLST), the most widespread genotyping methodology for bacterial pathogens, is used to describe the molecular epidemiology of leptospirosis in some countries or regions. 20,21 These approaches have potential to confirm the identity and genetic stability of bacterial strains over multiple vaccine seed passages. Therefore, the aims of the present study were to assess the genetic stability of leptospiral vaccine strains by using PFGE and MLST.…”
mentioning
confidence: 99%
“…MLST was performed on 7 housekeeping genes (including glmU, pntA, sucA, tpiA, pfkB, mreA, and caiB) as previously described. 20 PCR amplification of MLST target genes was performed in a volume of 50 ml and contained a final concentration of 1.5-3.5 mM MgCl 2 , 0.2 mM dNTP, 1 unit Taq DNA polymerase (Takara, Dalian, China), 0.25 mM of each primer, and 20-50 ng of Leptospira DNA. Amplification was performed under the following thermocycler conditions: one cycle of 95 C for 2 min, 30 cycles each of 95 C for 10 s; 46 C for 15 s; and 72 C for 30 s, followed by a final period of 72 C for 7 min.…”
mentioning
confidence: 99%